A Novel Chemically-Modified Curcumin 2.24: Short-Term Systemic Therapy for Natural Periodontitis in Dogs - Deng, Jie; Golub, Lorne M.; Lee, Hsi-Ming; Bhatt, Heta-Dinesh; Hong, Hou-Lin; Johnson, Francis; Scaduto, Joseph; Zimmerman, Thomas; Gu, Ying (Frontiers in Dental Medicine, 2021)
Periodontitis, a destructive periodontal inflammatory disease, negatively impacts oral-health related quality of life. It's characterized by the generation of inflammatory mediators and the excess-production of collagenolytic tissue-destructive enzymes (especially matrix metalloproteinases, MMPs). Many biomarkers can be used to define/diagnose disease progression. However, there is still a critical lack of specific, fast, and reliable biomarkers that correlate well with early response to treatment, which can be used to predict/monitor disease. Here, we report that an early marker, MMP-9, was found to be sensitive in response to a 1-month systemic therapy of CMC2.24, a novel chemically-modified curcumin, in beagle dogs with naturally-occurring periodontitis. In brief, eight adult female dogs with generalized periodontitis were distributed into placebo and treatment groups (n = 4/group). After a 1-h full-mouth scaling and root planing at time 0, placebo or CMC2.24 (10 mg/kg) capsules were orally-administered once/day for 1-month. Clinical periodontal parameters were measured at time 0 and 1-month; in addition, peripheral blood samples from these dogs were collected and analyzed for the pro-, activated-, and total-forms of MMP-9 by gelatin zymography. Interestingly, we found that the 1-month systemic therapy of CMC2.24 did appear to significantly reduce both pro- and activated-MMP-9 in peripheral blood at this early stage compared to placebo, prior to apparent clinical improvements seen at a later stage in a previous study (3-months). Thus, MMP-9 may serve as an early/sensitive biomarker that can precede/predict future clinical changes in disease severity and response to treatment which we observed in the long-term study in this dog model of natural periodontitis.